2019
DOI: 10.3390/cells8080888
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stress-Induced Multiple Multipolar Divisions of Human Cancer Cells

Abstract: Multipolar divisions of heated cells has long been thought to stem from centrosome aberrations of cells directly caused by heat stress. In this paper, through long-term live-cell imaging, we provide direct cellular evidences to demonstrate that heat stress can promote multiple multipolar divisions of MGC-803 and MCF-7 cells. Our results show that, besides facilitating centrosome aberration, polyploidy induced by heat stress is another mechanism that causes multipolar cell divisions, in which polyploid cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 60 publications
(96 reference statements)
0
4
0
Order By: Relevance
“…The misalignment of chromosomes followed by mitotic slippage is known to induce G1 arrest and cell death [53]. Hyperthermia produces chromosomal misalignment and mitotic slippage in cells [54,55]. However, the underlying mechanism for the chromosome misalignment is yet to be understood.…”
Section: Prolonged Hyperthermia Leads To Chromosomal Misalignment In mentioning
confidence: 99%
“…The misalignment of chromosomes followed by mitotic slippage is known to induce G1 arrest and cell death [53]. Hyperthermia produces chromosomal misalignment and mitotic slippage in cells [54,55]. However, the underlying mechanism for the chromosome misalignment is yet to be understood.…”
Section: Prolonged Hyperthermia Leads To Chromosomal Misalignment In mentioning
confidence: 99%
“…These findings are related to cancer, as heat-stressed cells resemble the cancer phenotype; at the same time, heat treatment is a potential therapy for the treatment of tumors. Heat treatment has been long regarded as an important treatment option for cancer [ 60 ]; however, there are cons involving heat treatment, e.g., studies have reported multipolar divisions in cancer cells, ultimately facilitating tumor heterogeneity [ 61 ]. An interplay of the energy metabolic dynamism was reported in hyperthermia-resistant ovarian cancer cells [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are very related to cancer, as heat stressed cells resembles the cancer phenotype and at the same time heat treatment is a potential therapy for treatment of tumors. Heat treatment is long regarded as an important treatment option for cancer [56], however, there cons of heat treatment too, like studies reporting multipolar divisions in cancer cells, ultimately facilitating tumor heterogeneity [57]. An interplay of energy metabolic dynamism is reported in hyperthermia-resistant ovarian cancer cells [58].…”
Section: Discussionmentioning
confidence: 99%